Analisis Keputusan Pembelian Smartphone pada Generasi Z - Habibie, Fachrul Husain; Aryapranata, Ariawan; Sakti, Pricilia Johani (Universitas Islam Kadiri, 2024)
Technological developments have brought significant changes to consumption patterns, especially among Generation Z who are known to be very technology savvy. One of the important consumption decisions for them is choosing a smartphone. This research aims to analyze the factors that influence smartphone purchasing decisions among Generation Z students at the Trisakti Tourism Institute, with a focus on four main variables, namely price, quality, features and brand. The approach used is quantitative with multiple regression analysis methods. Data collection was carried out by distributing questionnaires to 150 student respondents, which were analyzed using classical assumption tests, validity and reliability tests, and multiple regression. The research results show that price, quality, features and brand have a significant influence on smartphone purchasing decisions, with brand having the greatest influence. Generation Z tends to choose smartphones that offer a combination of affordable prices, good quality and advanced features, and prefers well-known brands. In conclusion, smartphone manufacturers need to consider these four factors when designing marketing strategies. Advice for students to be wiser in choosing products that suit their needs and budget. For manufacturers, it is important to continue to innovate and strengthen their brand image. Lecturers are expected to be able to use these findings in teaching related to consumer behavior.